Integrated Analysis of the Alterations in Gut Microbiota and Metabolites of Mice Induced After Long-Term Intervention With Different Antibiotics - Zhang, Nan; Liu, Jun; Chen, Zhiyun; Chen, Ning; Gu, Fangyan; He, Qiushui (Frontiers in Microbiology, 2022)
Objectives: We aimed to study the effect of antibiotic-induced disruption of gut microbiome on host metabolomes and inflammatory responses after long-term use of antibiotics. Methods: Three groups of 3-week-old female C57BL/6 mice (N=44) were continuously treated with vancomycin (VAN), polymyxin B (PMB) or water, respectively, for up to 28 weeks. Fecal samples collected at different time points were analyzed by bacterial 16S rRNA gene sequencing and untargeted metabolomics by ultraperformance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC Q-TOF MS). Serum cytokines (IFN-γ, IL-2, IL-10, IL-13, IL-17A and TNF-α) were determined by multiplex immunoassay. Results: Treatment by VAN or PMB did not affect the average body weight of mice. However, a heavier caecum observed in VAN-treated mice. Compared with PMB-treated and control mice, VAN treatment induced more rapid dysbiosis of gut microbiota and dysmetabolism. Instead of Bacteroides, VAN-treated mice had a compositional shift to Proteobacteria and its species Escherichia coli and Verrucomicrobia and its species Akkermansia muciniphila. The shift was accompanied by decreased richness and diversity in microbiota. PMB-treated mice had an increased Firmicutes, and the diversity was shortly increased and further decreased to the baseline. Decreased levels of short-chain and long-chain fatty acids, bile acids, L-arginine, dopamine, L-tyrosine and phosphatidylcholine (all P values < 0.05) were observed in VAN-treated mice. In contrast, significantly increased levels of amino acids including L-aspartic acid, beta-alanine, 5-hydroxy-L-tryptophan, L-glutamic acid and lysophosphatidylcholines (all P values < 0.05) were found. These changes occurred after 3-week treatment and remained unchanged up to 28 weeks. For PMB-treated mice, metabolites involved in the metabolic pathway of vitamin B6 were decreased, while glycocholic acid and chenodeoxycholic acid were increased (all P values < 0.05). After 8-week treatment, VAN-treated mice had significantly higher levels of serum IFN-γ, IL-13 and IL-17A, and PMB-treated mice had higher levels of IL-13 and IL-17 compared to control mice. At 28-week treatment, only IL-17A remained high in PMB-treated mice. Conclusion: This study showed the antibiotics-induced alterations in gut microbiota contribute to host inflammatory responses through the change in metabolic status, which are likely related to the type, rather than timing of antibiotic used.